Recovery from nerve injury induced behavioral hypersensitivity in rats parallels resolution of abnormal primary sensory afferent signaling - Boada, M. Danilo; Martin, Thomas J.; Parker, Renee; Houle, Timothy T.; Eisenach, James C.; Ririe, Douglas G. (Pain (Amsterdam), 2020)
Pain and hypersensitivity months after peripheral injury reflect abnormal input from peripheral afferents likely in conjunction with central sensitization. We hypothesize that peripheral changes occur in defined sensory afferents and resolve as behavioral response to injury resolves. Male Sprague–Dawley rats underwent sham or partial L5 spinal nerve ligation, and paw withdrawal threshold (PWT) was sequentially measured during recovery. At 2, 4, 8, and 12 weeks after injury, randomized animals underwent electrophysiologic assessment of L4 fast-conducting high- and low-threshold mechanoreceptors, and individual neuronal mechanical thresholds (MTs) were contrasted with PWTs in the same animals. Paw withdrawal thresholds decreased after injury and resolved over time ( P < 0.001). Similarly, MTs of fast-conducting high-threshold mechanoreceptors decreased after injury and resolved over time ( P < 0.001). By contrast, MTs of low-threshold mechanoreceptors increased after injury and resolved over time ( P < 0.001). Distributions of recordings from each afferent subtype were perturbed after injury, and this too resolved over time. After resolution of behavioral changes, several electrical abnormalities persisted in both neuronal subtypes. These data extend previous findings that mechanically sensitive nociceptors are sensitized, whereas tactile, largely Aβ afferents are desensitized after nerve injury by showing that the time course of resolution of these changes mirrors that of behavioral hypersensitivity in a surgical injury including neural damage. These data support a role of abnormal peripheral input, from both nociceptor and tactile afferents, during recovery from peripheral injury and underscore the potential importance of both classes of afferents as potential targets for pain treatment.